Sugarwin: A Sugarcane Insect-Induced Gene with Antipathogenic Activity - Ane H. Medeiros; Flávia P. Franco; Juliana L. Matos; Patrícia A. de Castro; Ludier K. Santos-Silva; Flávio Henrique-Silva; Gustavo H. Goldman; Daniel S. Moura; Marcio C. Silva-Filho (Molecular Plant-Microbe Interactions, 2012)
In sugarcane fields, colonization of the stalk by opportunistic fungi usually occurs after the caterpillar Diatraea saccharalis attacks the sugarcane plant. Plants respond to insect attack by inducing and accumulating a large set of defense proteins. Two homologues of a barley wound-inducible protein (BARWIN), sugarcane wound-inducible proteins SUGARWIN1 and SUGARWIN2, have been identified in sugarcane by an in silico analysis. Antifungal properties have been described for a number of BARWIN homologues. We report that a SUGARWIN::green fluorescent protein fusion protein is located in the endoplasmic reticulum and in the extracellular space of sugarcane plants. The induction of sugarwin transcripts occurs in response to mechanical wounding, D. saccharalis damage, and methyl jasmonate treatment. The accumulation of transcripts is late induced and is restricted to the site of the wound. Although the transcripts of sugarwin genes were strongly increased following insect attack, the protein itself did not show any effect on insect development; rather, it altered fungal morphology, leading to the apoptosis of the germlings. These results suggest that, in the course of evolution, sugarwin-encoding genes were recruited by sugarcane due to their antipathogenic activity. We rationalize that sugarcane is able to induce sugarwin gene expression in response to D. saccharalis feeding as a concerted plant response to the anticipated invasion by the fungi that typically penetrate the plant stalk after insect damage.